2015
DOI: 10.1128/jb.00127-15
|View full text |Cite
|
Sign up to set email alerts
|

Copper Tolerance and Characterization of a Copper-Responsive Operon, copYAZ , in an M1T1 Clinical Strain of Streptococcus pyogenes

Abstract: Infection with Streptococcus pyogenes is associated with a breadth of clinical manifestations ranging from mild pharyngitis to severe necrotizing fasciitis. Elevated levels of intracellular copper are highly toxic to this bacterium, and thus, the microbe must tightly regulate the level of this metal ion by one or more mechanisms, which have, to date, not been clearly defined. In this study, we have identified two virulence mechanisms by which S. pyogenes protects itself against copper toxicity. We defined a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 78 publications
3
29
0
Order By: Relevance
“…The present work focused on evaluating the role of CopA in S. suis resistance to Cu stress. Our data clearly demonstrated that CopA protects S. suis against Cu toxicity, as based on the following lines of evidence: (i) S. suis CopA shares a high level of identity (approximately 50%) with its homologues from other streptococcal species, all of which are involved in Cu export [17,18,19,20,21]; (ii) S. suis upregulates copA expression in response to Cu; (iii) the Δ copA mutant exhibits increased sensitivity to Cu stress both in liquid media and on agar plates; (iv) the Δ copA mutant forms less colonies after treatment with Cu; and (v) addition of Cu to the medium leads to a higher level of intracellular Cu in the Δ copA mutant.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The present work focused on evaluating the role of CopA in S. suis resistance to Cu stress. Our data clearly demonstrated that CopA protects S. suis against Cu toxicity, as based on the following lines of evidence: (i) S. suis CopA shares a high level of identity (approximately 50%) with its homologues from other streptococcal species, all of which are involved in Cu export [17,18,19,20,21]; (ii) S. suis upregulates copA expression in response to Cu; (iii) the Δ copA mutant exhibits increased sensitivity to Cu stress both in liquid media and on agar plates; (iv) the Δ copA mutant forms less colonies after treatment with Cu; and (v) addition of Cu to the medium leads to a higher level of intracellular Cu in the Δ copA mutant.…”
Section: Discussionsupporting
confidence: 61%
“…In S. suis 2 strain SC19, CopA encoded by the B9H01_RS06680 locus had 54%, 52%, and 45% amino acid sequence identity to CopA from S. mutans , S. pyogenes , and S. pneumoniae , respectively. In S. mutans , S. gordonii , and S. pyogenes , the genes copY (encoding a Cu-responsive transcriptional regulator), copA , and copZ (encoding a Cu chaperone protein) form a Cu-responsive operon, copYAZ (Figure 1) [17,18,19,21]. In S. pneumoniae , a cupA gene (encoding a hypothetical protein) is present in the operon instead of copZ (Figure 1) [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of Fe(II), one aspect of the bacterial peroxide stress response involves the decreased expression of Fe uptake systems and the increased expression of Fe storage proteins that effectively sequester Fe and thus prevent prooxidant activity (12)(13)(14). In contrast, copper concentrations within the bacterial cell are held very low as a consequence of the action of a Cu efflux system (CopYAZ) that is controlled by a Cu-sensing regulator (CopY) (15)(16)(17). The possibility that Fe ions might also be effluxed from the bacterial cell during peroxide stress has not been widely investigated.…”
mentioning
confidence: 99%